Effect of native strains of plant growth promoting rhizobacteria on growth and yield of Isabgol (Plantago ovata) - MISHRA, BRIJESH K; SINGH, BALRAJ; RANJAN, J K; DUBEY, P N; KANT, K; JOSHI, ARUNABH (The Indian Journal of Agricultural Sciences, 2016)
An experiment was conducted to evaluate the growth promotion in isabgol (Plantago ovata Forsk.) with native rhizobacteria strains (ISB-2, ISB-5, ISB-8, ISB-9, ISB-10, ISB-125, ISB-15 and ISB-28) isolated from the rhizospheric soils collected from western semi-arid region of India. These isolates were tested for their indole acetic acid production, insoluble phosphate solubilization and ability to promote germination of isabgol seeds under controlled conditions. Three rhizobacterial isolates (IBS-5, IBS-9 and IBS-28) were found promising towards enhancing the growth and yield of isabgol plants. The isolate ISB-5 was identified as Azotobacter vinelandii, ISB-9 as Pseudomonas stutzeri, and ISB-28 as Bacillus aryabhattai based upon their biochemical and molecular characterization. The highest seedling vigour index was recorded for B. aryabhattai (316.52±3.02) followed by A. vinelandii (310.22±7.56) and the lowest seedling vigour was recorded with ISB-10 which was found to be at par with control. The maximum shoot dry weight at harvest was recorded with B. aryabhattai (2.33g) being at par with P. stutzeri and the minimum shoot dry weight was for control. The highest seed yield per plant (0.72 g) was observed with B. aryabhattai followed by A. vinelandii(0.61 g).